PENGUATAN UMKM MELALUI STRATEGI BRANDING PADA TEMPE TAHU PANTURA DESA TEGALREJO, PROBOLINGGO - Rahmatika, Ajeng Dian; Pertiwi, Tri Kartika (INCIDENTAL : Journal Of Community Service and Empowerment, 2023)
Micro, Small and Medium Enterprises (MSMEs) are one of the activities that can have an impact on the country's economy. MSMEs can move faster if they can take advantage of advances in technology. This utilization can be in the form of branding through Digital Marketing on a product. Having a business but no product branding, then the business activities are less than optimal. Branding is needed in a business to be able to compete with other competitors. Branding is a business activity where company communication with consumers occurs. This activity intends to introduce a brand from the company with the aim of enlarging and strengthening the brand. In strengthening the brand, you can do Digital Marketing and making a business logo. The existence of this Community Service activity is aimed at product branding activities for MSMEs in Tegalrejo Village, Probolinggo. These MSMEs are Tempe Tahu 'Pantura' MSMEs engaged in the culinary field. This activity is carried out with various methods, namely lMSMEs survey, socialization, mentoring, and submission of achievements. The obstacle faced by these MSMEs is the lack of maximum product marketing carried out. This Community Service aims to introduce and apply branding to products. From these activities, it is hoped that it can have a positive impact on the development of MSMEs.